Work Values Ethic, GNP Per Capita and Country of Birth Relationships - McMurray, Adela J. (Journal of business ethics, 2013)
Workplaces around the world have experienced extraordinary changes to the composition of their workforces and the nature of work. Few studies have explored workers from multiple countries of birth, with multiple religious orientations, working together within a single country of residence. Building on and extending the Work Values Ethic (WVE) literature, we examine 1,382 responses from employees working in three manufacturing companies. Differences were found in the mean WVE scores of groups of respondents from 42 countries of birth. Their WVE scores were strongly associated with their birth countries’ per capita Gross National Product (GNP), and the means of these scores did not change with variations in the respondents’ length of residence in a different country. These results have implications for developing cross-cultural management practices and for improving relationships with employees, with opportunities for increased commitment and, potentially, productivity.